State of competition: conceptual shoehorning behind priority on calcitonin precursor biosynthesis - Enrique Wulff (Studia Historiae Scientiarum, 2019)
Until the 1950s, the first results in the studies of calcitonin-thyrocalcitonin were ignored in the accepted research scheme. However, it was José Fernández Nonídez from the Spanish School of Histology, died in Augusta (Georgia, USA) in 1947, whose expertise in the parafollicular cells of the mammalian thyroid had led him to an advanced understanding of this separate endocrine organ, which secretes calcitonin. The antecedent of the secretion was present in the cytoplasm of these cells, which Nonídez explained in a paper published in 1932.